The group II metabotropic glutamate receptor agonist LY354740 and the D2 receptor antagonist haloperidol reduce locomotor hyperactivity but fail to rescue spatial working memory in GluA1 knockout mice - Börner, Thomas; Sprengel, Rolf; Seeburg, Peter H. (European journal of neuroscience, 2017)
Group II metabotropic glutamate receptor agonists have been suggested as potential anti-psychotics, at least in part, based on the observation that the agonist LY354740 appeared to rescue the cognitive deficits caused by non-competitive N-methyl-d-aspartate receptor (NMDAR) antagonists, including spatial working memory deficits in rodents. Here, we tested the ability of LY354740 to rescue spatial working memory performance in mice that lack the GluA1 subunit of the AMPA glutamate receptor, encoded by Gria1, a gene recently implicated in schizophrenia by genome-wide association studies. We found that LY354740 failed to rescue the spatial working memory deficit in Gria1−/− mice during rewarded alternation performance in the T-maze. In contrast, LY354740 did reduce the locomotor hyperactivity in these animals to a level that was similar to controls. A similar pattern was found with the dopamine receptor antagonist haloperidol, with no amelioration of the spatial working memory deficit in Gria1−/− mice, even though the same dose of haloperidol reduced their locomotor hyperactivity. These results with LY354740 contrast with the rescue of spatial working memory in models of glutamatergic hypofunction using non-competitive NMDAR antagonists. Future studies should determine whether group II mGluR agonists can rescue spatial working memory deficits with other NMDAR manipulations, including genetic models and other pharmacological manipulations of NMDAR function.